Synbiotics in the Management of Pediatric Gastrointestinal Disorders: Position Paper of the ESPGHAN Special Interest Group on Gut Microbiota and Modifications. Issue 1 (28th January 2023) - Hojsak, Iva; Kolaček, Sanja; Mihatsch, Walter; Mosca, Alexis; Shamir, Raanan; Szajewska, Hania; Vandenplas, Yvan; ,
Abstract : Background: Synbiotics are a mixture comprising of live microorganisms and substrate(s) selectively utilized by host microorganisms that confers a health benefit on the host. There is an increasing number of studies investigating their role in different diseases and disorders. Aim: The purpose of this article is to provide recommendations for the use of synbiotics in the management of pediatric gastrointestinal disorders. The recommendations are developed by the ESPGHAN Special Interest Group on Gut Microbiota and Modifications. Methods: From existing literature databases, we searched and appraised all systematic reviews and/or meta-analyses, and subsequently published randomized controlled trials (RCTs) that compared the use of synbiotics, in all delivery vehicles and formulations, at any dose, compared to no synbiotics. Synbiotics which are part of infant formula were not assessed. The recommendations were formulated only if at least 2 RCTs that used a well-defined synbiotic were available. Results: Based on the currently available evidence, no recommendation can be formulated in favor or against the use of evaluated synbiotic combination in the treatment of acute gastroenteritis, prevention of necrotizing enterocolitis, Helicobacter pylori infection, inflammatory bowel disease, functional gastrointestinal disorders, and allergy in infants and children. Conclusions: There is a need for more, well-designed RCTs on the role of synbiotics in gastrointestinal disorders with the same outcome measures to enable the inter-studies comparisons.